Problem-Based Learning Module of Environmental Changes to Enhance Students’ Creative Thinking Skill - Pamula Guruh Prastiwa Anjarwati; Sajidan Sajidan; Baskoro Adi Prayitno (Biosaintifika: Journal of Biology & Biology Education, 2018)
Creative thinking skills are important for long-term success. Empowering creative thinking skills which can be trained through problem-solving activities in learning, thereby promoting high cognitive engagement. This study aimed to test the effectiveness of the research and development product of Problem-Based Learning module of environmental changes in empowering students’ creative thinking skills. The research method used was the Quasi-experiment with nonequivalent control group design. The sample of the research was the tenth-graders of a Senior High School in Karanganyar district, Central Java. The sampling was cluster sampling by involving two classes, namely the Grade X-MIA 1 with 28 students and the X-MIA 4 with 28 students. The qualitative and quantitative-descriptive approaches were used to analyze the data. The result shows the mean of creative thinking skills score of experiment group is higher than the control group. This developed module could empower students’ creative thinking skills by problem-solving activities as needed for Indonesian educational goal . The study concludes that development module was constructed based on Problem-based Learning activities in the module could stimulate students solved and identified the problems with their ideas and developed their creative thinking.